ISLAMIC BRAND TRUST IN MUSLIM CONSUMER BEHAVIOR: A SYSTEMATIC LITERATURE REVIEW - Zulfa Khairina Batubara; M. Shabri Abd. Majid; Andri Soemitra (Smart Education, 2025)
Abstract: This study aims to systematically evaluate the literature discussing Islamic Brand Trust in Muslim consumer behavior. Using a Systematic Literature Review (SLR) approach based on the PRISMA method, this study analyzed 50 scientific articles published between 2018 and 2025. The results of the study revealed that brand trust in the Islamic context is not only influenced by general elements such as product quality and brand communication, but also significantly influenced by Islamic values such as halal, sharia ethics, consumer religiosity, and the credibility of halal certification institutions. This study identified five main themes: the role of trust as a mediator, the importance of halal certification, Islamic ethical values in branding, the role of religiosity, and trust in the digital ecosystem. This study contributes to the Islamic marketing literature and offers practical recommendations for marketers in building brand trust in the Muslim consumer segment. Keyword: Islamic branding, brand trust, muslim consumer behavior, systematic literature, PRISMA. Abstrak: Penelitian ini bertujuan untuk mengevaluasi secara sistematis literatur yang membahas Islamic Brand Trust dalam perilaku konsumen Muslim. Dengan menggunakan pendekatan Systematic Literature Review (SLR) berbasis metode PRISMA, penelitian ini menganalisis 50 artikel ilmiah yang diterbitkan antara tahun 2018 hingga 2025. Hasil kajian mengungkapkan bahwa brand trust dalam konteks Islam tidak hanya dipengaruhi oleh elemen umum seperti kualitas produk dan komunikasi merek, tetapi juga dipengaruhi secara signifikan oleh nilai-nilai Islami seperti kehalalan, etika syariah, religiusitas konsumen, serta kredibilitas lembaga sertifikasi halal. Studi ini menemukan lima tema utama: peran trust sebagai mediator, pentingnya sertifikasi halal, nilai-nilai etika Islami dalam branding, peran religiusitas, serta trust dalam ekosistem digital. Studi ini memberikan kontribusi terhadap literatur pemasaran Islami dan menawarkan rekomendasi praktis bagi pemasar dalam membangun kepercayaan merek di segmen konsumen Muslim. Kata kunci: Islamic branding, brand trust, perilakiu konsumen Muslim, literatur sistematis, PRISMA.